ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH RIGHT ISSUE - Fajar Nur Iman; Yenny Ernitawati; Nasiruddin Nasiruddin (JURNAL ILMIAH NUSANTARA, 2024)
Right issue is a capital raising strategy by issuers to obtain additional funds from existing shareholders with the aim of improving or increasing the company's financial performance. This study is intended to analyze the difference in the company's financial performance between the period before and after the right issue, which is measured for 1 year before and 1 year after. Financial performance is proxied by current ratio, debt to equity ratio, total assets turnover, and return on assets. This research applies a quantitative approach with a comparative method. The population used was 89 companies listed on the IDX from the non-financial sector that conducted a rights issue for the 2015-2021 period. A sample of 68 companies was obtained using purposive sampling technique. The data analysis technique uses descriptive statistics, normality test, and t-test with the help of SPSS 20 software. The test results show that financial performance with the current ratio (CR) and debt to equity ratio (DER) proxies is different between the period before and after the right issue. However, financial performance with total assets turnover (TATO) and return on assets (ROA) proxies does not differ between the period before and after the right issue.